Reasons that led hypertensive elderly to seek assistance in primary care - Roberta Fernanda Rogonni Ferrari; Daysi Mara Murio Ribeiro; Fabiana Cristina Vidigal; Sonia Silva Marcon; Vanessa Denardi Antoniassi Baldissera; Ligia Carreira (Rev Rene)
We aimed at verifying the complaints causing elderly hypertensive patients search for a health center in a municipality of the state of Paraná-Brazil. Analytical and exploratory retrospective study conducted between November 2013 and January 2014, with 106 records of elderly hypertensive who underwent nursing consultation in the past five years. Elderly females (73.5%), up to 70 years (61.3%), with a partner (57.5%) and up to 4 years of study (73.5%) accounted for most of the sample. The main complaints causing elderly hypertensive patients to seek health care focused on endocrine and nutritional diseases (36%). A significant association between sex and search the health service having hypertension as a major complaint, but no association was observed between complaints related to hypertension and number of interventions prescribed by nurses. The data revealed enable the planning of specific interventions to the needs of elderly hypertensive allowing adjustments in care.